Molecular pathways to high-level azithromycin resistance in Neisseria gonorrhoeae. (24th March 2021) - Laumen, J G E; Manoharan-Basil, S S; Verhoeven, E; Abdellati, S; De Baetselier, I; Crucitti, T; Xavier, B B; Chapelle, S; Lammens, C; Van Dijck, C; Malhotra-Kumar, S; Kenyon, C
Abstract: Background: The prevalence of azithromycin resistance in Neisseria gonorrhoeae is increasing in numerous populations worldwide. Objectives: To characterize the genetic pathways leading to high-level azithromycin resistance. Methods: A customized morbidostat was used to subject two N. gonorrhoeae reference strains (WHO-F and WHO-X) to dynamically sustained azithromycin pressure. We tracked stepwise evolution of resistance by whole genome sequencing. Results: Within 26 days, all cultures evolved high-level azithromycin resistance. Typically, the first step towards resistance was found in transitory mutations in genes rplD, rplV and rpmH (encoding the ribosomal proteins L4, L22 and L34 respectively), followed by mutations in the MtrCDE-encoded efflux pump and the 23S rRNA gene. Low- to high-level resistance was associated with mutations in the ribosomal proteins and MtrCDE efflux pump. However, high-level resistance was consistently associated with mutations in the 23S ribosomal RNA, mainly the well-known A2059G and C2611T mutations, but also at position A2058G. Conclusions: This study enabled us to track previously reported mutations and identify novel mutations in ribosomal proteins (L4, L22 and L34) that may play a role in the genesis of azithromycin resistance in N. gonorrhoeae .